1080 Evaluating the effectiveness of paediatric emergency simulation training for medical students. (17th August 2022) - Shetty, Samiksha; Chan, Alex; Gupta, Ritu
Abstract : Aims: High-fidelity simulation training is a well-established method of developing confidence and competence in the safe management of paediatric emergencies. 1 We designed and delivered a simulation course for Year 5 medical students on their paediatric clinical placement at a district general hospital, focusing on common paediatric emergency scenarios. Our aim is to evaluate the relevance, experience, and value of simulation as a teaching modality in undergraduate paediatric education, as well as the effectiveness of the course in preparing students to manage paediatric emergencies as foundation doctors. Methods: The sessions took place in the hospital's high-fidelity simulation suite, using scenarios from the paediatric emergency simulation course for junior doctors and adapting their level of complexity for medical students. The students were briefed on the simulation process and the relevance of human factors in clinical practice. They participated in each simulation scenario as a pair, under the instruction that they approach each situation as a newly qualified foundation doctor working in paediatrics. Each scenario was followed by a structured debrief session, where participants were encouraged to reflect on their performance and receive feedback from their peers and the simulation facilitator. They also received didactic teaching on the approach to managing common scenarios such as diabetic ketoacidosis, severe asthma, and sepsis. Students completed anonymised feedback forms, rating statements pertaining to the four domains of the course ('Content', 'Simulation', 'Feedback', and 'Overall') on a 5-point Likert scale, as well as written feedback on the session. This course was delivered three times to a total of 15 students. Results: The students rated this course with an overall average score of 4.95/5, with each domain consistently rated at an average of above 4.91/5 ( figure 1 ). All students (15/15) strongly agreed that they gained knowledge that was transferrable to the clinical setting, and 14/15 either agreed or strongly agreed that the simulation session better prepared them to recognise unwell children. The word cloud summarises the written feedback on what students liked about the course and what could be improved ( figure 2 ). The students particularly valued the opportunity to apply their theoretical knowledge to clinical practice, the realism of the simulation scenarios, and relevance of the content to their curriculum. They appreciated the supportive learning environment and useful feedback received on their clinical and non-technical skills, such as teamwork and communication. Overwhelmingly, their suggestions for improvement was to have more, regular simulation sessions exploring different paediatric scenarios. Conclusion: Our results reflect a significant self-reported positive impact of paediatric emergency simulation education on medical students. We aim to further develop these sessions for medical students, to help improve their preparedness in recognising and managing acutely unwell children and young people. Reference: Clerihew L, Rowney D, Ker JSimulation in paediatric trainingArchives of Disease in Childhood. Education and Practice 2016;101:8-14.